First Report of Bacterial Wilt Caused by Ralstonia solanacearum Biovar 2 Race 1 on Tomato in Egypt - Mohamed A. A. Seleim; Kamal A. M. Abo-Elyousr; Kenawy M. Abd-El-Moneem; Farag A. Saead (The Plant Pathology Journal, 2014)
This study aims to isolate and identify the causal pathogen of tomato bacterial wilt in Egypt. In 2008, tomato plants showing typical symptoms of bacterial wilt disease with no foliar yellowing were observed in Minia, Assiut and Sohag governorates, Egypt. When cut stems of symptomatic plants were submerged in water, whitish ooze was evident and longitudinal sections showed a brown discoloration in the vascular tissues. Bacteria were isolated on triphenyl tetrazolium chloride medium and fifteen isolates shown typical morphological and cultural characteristics were confirmed as Ralstonia solanacearum biovar 2 race 1. Pathogenicity tests showed that all isolates proved to be pathogenic to tomato plants, varied from 52 to 97% wilting. This is the first report of R. solanacearum biovar 2 race 1 causing bacterial wilt in tomato crop in Egypt.